Synthesis of an S-Adenosylmethionine-cleaving Enzyme in T3-infected Escherichia coli and Its Disturbance by Co-infection with Enzymatically Incompetent Bacteriophage - Hausmann, Rudolf (1967)
Synthesis of an S-adenosylmethionine-cleaving enzyme evoked by infection of Escherichia coli with phage T3 was independent of the multiplicity of infection with the wild type, T3 sam(+). It was depressed, however, by mixed infection with related phages genetically incapable of directing enzyme production, such as T3 sam(−), or phage T7. The depressor effect of enzymatically incompetent genomes depended on their proportion among the input phage and not on their absolute multiplicity. The effect was more pronounced with homologous, enzymatically incompetent phage (T3 sam(−)) than with heterologous phage (T7). After ultraviolet irradiation, enzymatically incompetent genomes lost their depressing power; at a survival level of 10(−7), no depression by either homologous or heterologous phage upon T3 sam(+)-directed enzyme synthesis was detected.